Thielaviopsis Trunk Rot of Palm - Monica L. Elliott (EDIS)
Thielaviopsis paradoxa is a fungus that can infect any part of a palm, and so can cause numerous diseases. In Florida, the two most frequent (and usually lethal) Thielaviopsis diseases observed in the landscape and field nursery are a bud (heart) rot and trunk rot. Thielaviopsis bud rot is discussed at http://edis.ifas.ufl.edu/pp144. This document is PP-219, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.